Democracy and Citizen Participation: A Comparative Study Between Peru and Ecuador - Rosa Clavijo-López; José Joel Cruz-Tarrillo; Raúl Alfredo Sánchez Ancajima; Fernando Escobedo; Carlos Miguel Aguilar Saldaña; José Enrique Armas Barrante; Tony Venancio Pereyra Gonzales; César Augusto Flores Tananta (My University, 2025)
Democracy is a fundamental part of a society, and it refers to the condition in which citizens exercise their autonomy. This research aimed to analyze the effect of democratic management on citizen participation. The study was approached from the positivist paradigm, with a non-experimental cross-sectional design; the participants were 416 Peruvians and 105 Ecuadorians. An exploratory analysis was carried out to determine the factorial structure of the constructs, and a confirmatory analysis was conducted for its validity. Subsequently, the structural equation model (SEM) was applied to test the hypotheses. The results present a three-dimensional structure (Citizenship legislation, Representative and responsible Government, Civil society and participation) of the democratic management variable. Likewise, the citizen participation variable presents a three-dimensional structure (opinionative, associative, Electoral-Partisan). On the other hand, the SEM model presents an adequate fit with an x2/df = 4.248, TLI is 0.911, CFI= 0.929, and RMSEA= 0.080. The hypothesis tests show an influence of democratic management on optimistic citizen participation with a ? of 0.861 and a significance of 0.000 (p<0.001) in the associative participation of citizens with a ? of 0.678 and a statistical significance of 0.000 (p<0.001), and democratic participation with a ? of 0.814 and 678 and a statistical significance of p<0.001. In conclusion, the results demonstrate the influence of these variables, highlighting the importance of strengthening democratic mechanisms for citizen participation. Received: 25 August 2024 / Accepted: 23 April 2025 / Published: 06 May 2025
Keywords: Democracy; Political science; Law; Politics; Democracy; Political science; Law; Politics; Social Sciences Social Sciences Sociology and Political Science Latin American socio-political dynamics; Social Sciences Social Sciences Communication Social Media and Politics; Social Sciences Social Sciences Political Science and International Relations Public Policy and Governance